Contributions of Structural Racism to the Food Environment: A Photovoice Study of Black Residents With Hypertension in Baltimore, MD. Issue 11 (15th November 2022) - Hines, Anika L.; Brody, Rebecca; Zhou, Zehui; Collins, Sarah V.; Omenyi, Chiazam; Miller, Edgar R.; Cooper, Lisa A.; Crews, Deidra C.
Abstract : Background: Disproportionate exposure to poor food environments and food insecurity among Black Americans may partially explain critical chronic disease disparities by race and ethnicity. A complex set of structural factors and interactions between Black residents and their food environments, including store types, quantity, proximity, and quality of goods and consumer interactions within stores, may affect nutritional behaviors and contribute to higher cardiovascular and kidney disease risk. Methods: We used the Photovoice methodology to explore the food environment in Baltimore, MD, through the perspectives of Black residents with hypertension between August and November 2019. Twenty-four participants were enrolled in the study (mean age: 65.1 years; 67% female). After a brief photography training, participants captured photos of their food environment, which they discussed in small focus groups over the course of 5 weeks. Discussions were audiotaped and analyzed for emergent themes using a line-by-line inductive approach. Themes were, then, organized into a collective narrative. Results: Findings describe physical and social features of the food environment as well as participants' perceptions of its origins and holistic and generational health effects. The study illustrates the interrelationships among the broader socio-political environment, the quality and quantity of stores in the food landscape, and the ways in which they engage with the food environment as residents and consumers who have been marginalized due to their race and/or social class. The following meta-themes emerged from the data: (1) social injustice; (2) structural racism and classism; (3) interpersonal racism; (4) generational effects; (5) mistrust; (6) social programs; and (7) community asset-based approaches, including advocacy and civic engagement. Conclusions: Understanding residents' perceptions of the foundations and effects of the food environment on their health may help stakeholders to cocreate multilevel interventions alongside residents to improve access to healthy food and health outcomes among disparities affected populations.